Lobbyism in the Political Process of Russia: Opportunities and Reality. / Cabildeo en el proceso político de Rusia: oportunidades y realidad. - RUSTЕMOVNA FATIKHOVADIANA; IVANOVICH OSTROUMOV, ALEKSANDR; FEDOROVNA OSTROUMOVA, OLGA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper examines the problem of the development of lobbyism as a political institution in modern Russia. and identifies their place and purpose. To achieve this goal, it is necessary to determine what transformations need to be carried out in the political life of Russian society, so that lobbyism acquires the features of a modern and efficient institution that actively promotes the development of business, society and the state. RESUMEN El artículo examina el problema del desarrollo del cabildeo como institución política en la Rusia moderna e identifica su lugar y propósito. Para lograr este objetivo, es necesario determinar qué transformaciones deben llevarse a cabo en la vida política de la sociedad rusa, para que el cabildeo adquiera las características de una institución moderna y eficiente, que promueva activamente el desarrollo de la empresa, la sociedad y el estado.